Pelatihan Aplikasi Canva untuk Mendukung Kreativitas Guru dalam Sistem Pembelajaran di SMPN 3 Wih Pesam - Richasanty Septima S; Ira Zulfa; Mustafa Kamal (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
Canva app is a graphic design platform that has become a favorite among users who don't have a graphic design background. With a variety of easy-to-use features and templates, Canva is perfect for teachers who want to create engaging and interactive learning materials. The purpose of building a Canva application is to make users easy to use and free of charge with hundreds of attractive design templates for the community. Canva is also a multifunctional application that can be used for the development of learning media. One of the main benefits of Canva app training is to increase teacher creativity in creating engaging learning. The methods used in this community service activity are discussion, training and practice. The results of this canva application training activity are (1) the canva application can improve the quality of learning materials delivered by teachers, (2) the canva application increases the attractiveness of learning, (3) the canva application can encourage teacher creativity better, (4) increase the use of technology for teachers in learning materials.